Integrasi Nilai-Nilai Islam dalam Kurikulum Nasional: Tantangan dalam Konteks Pendidikan di Indonesia - Wakib Kurniawan; Agus Wahyu Mulyanto; Bahrudin Yusuf Zen (Moral : Jurnal kajian Pendidikan Islam, 2025)
The integration of Islamic values ​​in the national curriculum is a strategic issue in the development of character education in Indonesia. Amidst the flow of globalization and technological advances, national education is faced with the challenge of maintaining national identity while responding to the needs of the times. This article aims to analyze the challenges of integrating Islamic values ​​in the national curriculum, especially in the context of the Independent Curriculum policy and the reality of multicultural education. Using a qualitative literature study approach, this article examines various national education literature and policies in the last five years. The results of the analysis show that the main challenges lie in the lack of pedagogical understanding of teachers, resistance to the integration of religious values ​​in general lessons, and limited contextual implementation guidelines. This article recommends the need for inclusive curriculum design, transformative teacher training, and strengthening collaboration between the government, educational institutions, and the community.